IFU spectroscopy of southern PN VI: the extraordinary chemo-dynamics of Hen 2-111. Issue 1 (9th December 2017) - Dopita, M A; Ali, A; Karakas, A I; Goldman, D; Amer, M A; Sutherland, R S
Abstract: In this paper, we present integral field spectroscopy of the extraordinary Type I bipolar planetary nebula Hen 2-111. In the lobes, we map fast-moving knots of material with [N ii ] λ6584/H α ratios up to 12, and with radial velocities relative to systemic from −340 up to +390 km s −1 . We find evidence of a bipolar ejection event at a velocity ∼600 km s −1 from the central star (assumed to be a binary), which occurred about 8000 yr ago. The fast-moving material is chemically quite distinct from the lower velocity gas in the bipolar lobes, and displays very high N abundances. We show that the fast-moving N-rich knots are not photoionized by the central star, and have constructed detailed shock models for the brightest knot. We find a pre-shock density ∼6 cm −3, and a shock velocity ∼150 km s −1 . The shock is not fully radiative, being only ∼600 yr old. This shocked gas is partially H-burnt, with helium abundance by mass exceeding that of hydrogen, and is interacting with partially H-burnt material ejected in an earlier episode of mass loss. We conclude that the high-velocity material and the bipolar shell must have originated during the late stages of evolution of a common-envelope phase in a close binary system.